The The Effectiveness of Audio Visual About SADARI on the Knowledge Level of Young Girls at AL-AMIN Wani High School - Juwita; Aisyah (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
In the city of Wani, according to the Association of Women with Breast Cancer (P2WPKP) 1,000 people suffer from this deadly disease, an increase from 273 cases of breast cancer in 2021. This cancer should be found at an earlier stage, however, 70% of cases of this cancer are often detected. at an advanced stage. Due to lack of knowledge about early detection of breast cancer through breast self-examination. Quantitative research, pre-experimental method, one group pretest-posttest. A sample of 30 respondents, Stratified Random Sampling technique. Univariate analysis showed that the respondent's knowledge before the intervention was good = 2, sufficient = 21, and less = 7. Changed after the intervention to be good = 18, enough = 11, and less = 1. Bivariate analysis using the Marginal Homogeneity There is a significant influence of audiovisual media about SADARI on the knowledge of young women at AL-AMIN Wani High School.